Salt Pricing Policy According to Islamic Justice Theory: Faridz Essack's Perspective - Mukhlish, Mukhlish; Ansori, Ansori; Aidonojie, Paul Atagamen; Asyiqoh, Lin; Saiful Abdullah (Al-Huquq: Journal of Indonesian Islamic Economic Law, 2025)
Legal issues regarding the unfairness of state policies in regulating salt prices need to be resolved, especially regarding the preparation of salt price regulations that favour the people's interests. The salt price policy should bring benefits to the people and not merely benefit the salt middlemen. This research contributes to reforming equitable regulations where the benchmarks are based on the theory of justice according to Farid Escak's theory. This research uses normative legal research methods by basing the argumentation on salt regulations and the concept of justice in Farid Escak's theory. The research produces essential findings in the form of a national salt price policy that does not bring benefits to farmers, but the policy favours the interests of middlemen and parties in the industrial sector (companies). In addition, the framework of policy regulation on equitable salt prices in Farid Escak's perspective produces ideas in the form of determining the price of salt must be in accordance with the needs of salt farmers and more oriented towards the welfare of farmers. This research recommends the need for the renewal of salt regulations to create justice in the determination of national salt prices.